Activating the Mobile User Interface With a Rule-Based Chatbot and EEG-Based Emotion Recognition to Aid in Coping With Negative Emotions - Haneen Reda Banjar; Lujain Alsefri; Aseel Alshomrani; Morouj Hamdhy; Sara Alahmari; Sanaa Sharaf (Human Behavior and Emerging Technologies)
Mental health depends on emotional intelligence (EI), the ability to recognize, understand, and manage emotions. As emotions—positive and negative—influence our actions, decisions, and health, EI has become more important in today’s fast-paced society. Negative emotions, in particular, pose a challenge due to their complexity and the difficulty in managing them effectively. The “Motus Up” mobile app represents a significant leap in personal mental health management by merging EEG-based emotion recognition with a rule-based chatbot to aid users in managing negative emotions. Utilizing principles of EI, the app customizes the mobile interface color settings, suggesting activities and providing advice suited to the user’s emotional state confirmed by the chatbot. The emotion recognition model is trained and tested using the SEED-IV dataset, ensuring compatibility with consumer EEG headbands and accurate detection of complex emotions like sadness and fear. Thorough static and dynamic testing has validated the app’s design and operational efficacy, confirming its preparedness for practical use. By combining real-time EEG data analysis with intelligent chatbot interactions, “Motus Up” stands out as an innovative mental health tool that enhances EI and offers a responsive experience for emotional self-regulation. This integration of technology and psychology in a mobile platform is poised to improve mental well-being and EI on a personal scale.